A life course perspective of victimization, child welfare involvement, cumulative stress and mental health for mothers on probation and parole. (December 2018) - Fedock, Gina; Garthe, Rachel C.; Sarantakos, Sophia; Golder, Seana; Higgins, George E.; Logan, T.K.
Abstract: Women involved in the criminal justice system experience multiple forms of adversity over their lifetimes. These events may include childhood abuse, involvement in the child welfare system as children, intimate partner violence victimization during adulthood, and punitive interactions with the child welfare system as mothers. Community supervision (e.g. probation or parole) entails particular stressors, such as obtaining basic needs and employment. A majority of women under community supervision also experience depression and anxiety. The current study used the Stress Process Model to investigate associations between childhood and adulthood stressors (including childhood abuse, intimate partner violence and child welfare system involvement), recent stressful life events, and symptoms of depression and anxiety for mothers (n = 348) on probation and parole. All of the mothers had experienced some form of childhood and/or adulthood victimization. Structural equation modeling was conducted to examine how childhood abuse, adulthood victimization, and child welfare system involvement as a child and a mother were associated with recent stressful life events and symptoms of depression and anxiety. Results indicated multiple direct and indirect relationships from childhood and adulthood stressors to mental health symptoms as women navigated probation and parole. For example, adverse childhood experiences were associated with elevated anxiety and depression symptoms via higher levels of recent stressful life events and adverse adulthood experiences. These findings highlight relationships between childhood abuse and adulthood factors and the mental health of mothers involved in the criminal justice system, with implications for theory, practice, and research.